A Population Based Study on the Prevalence of Cigarette Smoking and Smokers' Characteristics at Osogbo, Nigeria. (January 2013) - Adepoju, Ebenezer G; Olowookere, Samuel A; Adeleke, Najemdeen A; Afolabi, Olusegun T; Olajide, Folakemi O; Aluko, Olufemi O
Background: Cigarette smoking has been linked to several cancers worldwide. The characteristics of smokers have not been well documented among Nigerians. Objective: This study assessed the prevalence and characteristics of cigarette smokers among the residents of Osogbo, in southwestern Nigeria. Method: The study, a population based cross-sectional study of randomly selected consenting adult residents of Osogbo, was conducted in September of 2011. Data was collected using a semi-structured interviewer administered questionnaire on cigarette smoking. Results: A total of 759 respondents were interviewed. Mean age was 42.1 ± 12.5 years. There were 364 (48%) males and 395 (52%) females. About 22% had ever smoked while 8.7% were current smokers, smoking an average of 22.9 ± 10.1 cigarettes per day. Males constituted the majority of current smokers. Most smokers (71%) were introduced to smoking by friends and ill health was the most often reported reason for quitting. Conclusion: Cigarette smoking is commonly practiced among males in the studied population and awareness creation and advocacy should be conducted throughout the city in order to inform current smokers about the hazards and cumulative effects inherent in smoking.